Grassroots Innovation: Scenario, Policy and Governance - Ng, Boon-Kwee (Archīum Ateneo, 2022)
Grassroots Innovations (GRIs) mostly represent incremental changes that are supported by local values and culture. In this respect, government efforts to promote and strengthen GRIs movements should take into consideration customised and targeted policy instruments that are different from the traditional innovation and development agendas. Based on this principle – and in the context of three Southeast Asian countries such as Malaysia, Thailand and the Philippines – this paper attempts to investigate the current public policy contexts and common instrumental mechanisms for public interventions supporting GRIs. The governing context alluding to policy support is elaborated to provide a taxonomy of GRIs policy measures germane to political-governance windows. The findings show that Malaysia has explicit policy support for GRIs, whereas innovators in Thailand and the Philippines indirectly benefit from broader inclusive development and innovation policies. There are three scenarios of instrumental mechanisms supporting GRIs – these show the differences in approaches adopted by national governments in terms of their perception of GRIs, modes of intervention and outcome expectations. This paper also highlights several policy concerns useful for future endeavours regarding public interventions on GRIs and rural development.